2021
DOI: 10.1161/circulationaha.120.052209
|View full text |Cite
|
Sign up to set email alerts
|

Effects of n-3 Fatty Acid Supplements in Elderly Patients After Myocardial Infarction

Abstract: Background: High intake of marine n-3 polyunsaturated fatty acids (PUFA) has been associated with reduced risk of cardiovascular events; however, this has not been confirmed in patients with a recent acute myocardial infarction (AMI). Elderly patients are at particularly increased cardiovascular risk after MI, but few trials address this group specifically. Omega-3 fatty acids hold the potential to reduce cardiovascular events with limited adverse effects in this vulnerable group. The hypothesis wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
155
1
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 217 publications
(209 citation statements)
references
References 40 publications
7
155
1
4
Order By: Relevance
“…Additionally, the risk of AF was not reduced or even increased by ω-3 PUFA treatment in two recently published reports. 16 , 17 Therefore, the mechanism of action of ω-3 PUFAs is complex, and pathological factors (e.g., increased risk of bleeding) and protective factors exist simultaneously. Our study showed reduced serum ANGPTL4 levels in patients with AF compared with healthy controls.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the risk of AF was not reduced or even increased by ω-3 PUFA treatment in two recently published reports. 16 , 17 Therefore, the mechanism of action of ω-3 PUFAs is complex, and pathological factors (e.g., increased risk of bleeding) and protective factors exist simultaneously. Our study showed reduced serum ANGPTL4 levels in patients with AF compared with healthy controls.…”
Section: Discussionmentioning
confidence: 99%
“…Two Ω-3 trials were released in late 2020, which did not find any CV benefits of Ω-3 therapy in high-risk patients. OMEMI used a lower-dose intervention (1.8 g/day EPA + DHA in addition to standard medical care) in elderly patients (age 70–82) following acute MI (2–8 weeks) [ 49 ]. There was no statistically significant difference in outcomes between treatment and placebo groups, which may be explained by insufficient Ω-3 dosing.…”
Section: Late-breaking Trialsmentioning
confidence: 99%
“…EPA and DHA used individually (5 g × day −1 ) seemed to diminish infarct size, while a combination of both to a level of 5 g × kg −1 did not [ 23 ]. Supplementation of EPA+DHA to a level of 1.8 g/day −1 for elderly patients with a recent acute myocardial infarction did not reduce clinical events either [ 24 ]. This might be due to n-3 PUFAs’ competition for the same receptors or biased signaling as observed with some protein receptors [ 23 ].…”
Section: Polyunsaturated Fatty Acids and Human Healthmentioning
confidence: 99%